PREGNANCY INDUCED HYPERTENSION AND ASSOCIATED FACTORS AMONG FEMALE PATIENTS (International Journal of Food and Nutritional Sciences, 2022)
Background: Although complications of child birth pressure comprise one of the primary culprits of child and maternal mortality and death, they constitute a serious health issue in the medical population. The objective of this research will be to evaluate perinatal mortality bp young women but also its lifestyle factors who gave birth at the Medical College Hospital in Hyderabad.METHODS: At the Gynaecology and Obstetrics Medical Hospital in Hyderabad, the research was a cross-sectional examination. The hospitals chosen for the study were proportionately divided among the total sample size (416). Using a methodical sampling approach, sample members from a larger population are picked, the study's participants were recruited. Statistical significance was defined as P values of 0.05 or less.RESULTS: With 53.8% of pregnancies having multigravida and when it comes to points in the cycle, 74.3% fall around 37 and 41 days, pregnancy-induced hypertension was discovered in 7.9% of women using delivery services. Among prenatal women hospitalised for deliveries, just 1.3% had ever experienced pregnancy-induced hypertension (PIH), 0.8% had ever experienced gestational diabetes mellitus, 4.8% had had multiple pregnancies, 10.3% had ever experienced chronic hypertension, and 3.8% had ever experienced PIH—most commonly from their mothers, or 84.6%. 7.7% of respondents who had renal illness reported having experienced it in the past during their present pregnancy.CONCLUSION: Pregnancy-related hypertension was prevalent in 7.9% of the women who used delivery services. Gestational age, chronic renal illness, and a history of the condition in the family were all predictive factors for pregnancy-induced hypertension.